A Discrete Weighted Montgomery Identity and Ostrowski Type Inequalities for Functions of Two Variables - Aglić Aljinović, A.; Peˇcarić, J. (Sarajevo Journal of Mathematics, 2024)
A discrete analogue of the weighted Montgomery identity for functions of two variables is presented and used to obtain new discrete Ostrowski type inequalities. 2010 Mathematics Subject Classification. 26D15